Enhancement of Solubility and Dissolution Rate of Clopidogrel by Self-nanoemulsifying Drug Delivery System - Aparna, Adella (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: A self-nanoemulsifying drug delivery system (SNEDDS) has been explored to improve the solubility and dissolution rate of poorly water-soluble drug clopidogrel. Materials and Methods: Different formulations were prepared using an oil, surfactant, and cosurfactant in varying ratios. A pseudo-ternary phase diagram was constructed to identify the self-nanoemulsification region. Further, the resultant formulations were investigated for clarity, phase separation, drug content, % transmittance, globule size, freeze-thaw method, in vitro dissolution studies, particle size analysis, and zeta potential. Results: On the basis of particle size, zeta potential and dissolution profile and other studies, F6 was found to be the best formulation of clopidogrel SNEDDS. The particle size of the emulsion is a crucial factor in self-emulsification performance because it determines the rate and extent of drug release as well as absorption. The particle size of the optimized SNEDDS formulation was found to be 5.2 nm and zeta potential was found to be ‒29 mV which comply with the requirement of the zeta potential for stability. The % release from optimized SNEDDS formulation F6 was highest (98.93%) and faster than other SNEDDS formulations and pure drug substance (32%) indicating influence of droplet size on the rate of drug dissolution. The faster dissolution from SNEDDS may be attributed to the fact that in this formulation, the drug is a solubilized form and on exposure to dissolution medium results in small droplet that can dissolve rapidly. Fourier transform infrared data revealed no physicochemical interaction between drug and excipients. Conclusion: Thus, clopidogrel with SNEDDS formulation may be used for the improvement of solubility and dissolution rate for the effective management of heart disease.